Weather Station Data on the Juneau Icefield ... - Emily H Baker; Scott McGee; Seth W. Campbell; Jamie L Pierce; Christopher J. Mcneil (U.S. Geological Survey, 2019)
Measurements of meteorological data are made at many permanent camp facilities on the Juneau Icefield. This portion of the data release includes select weather data that has received basic quality control and assurance. Data is released at three different levels of processing, level 0, 1 and 2. Level 0 data contains compiled raw data, before QC procedures are applied, at the original timestep recorded by the instrument. Level 1 data has received a plausible value check, and minimal manual error identification (e.g. errors noted on field visits). Level 2 data has been through more extensive quality control procedures and is provided at both the original instrument timestep as well as aggregated hourly and daily values. Data at many JIRP sites consist of a single temperature sensor, recording in a Stevenson-type shield. Automated weather stations at Camp 10, 17, and 18 have measured additional meteorological variables in recent years. Both are presented in this data release. ...